PROVIDING INFORMATION ABOUT TEXTILES AND ITS HISTORY IN TECHNOLOGY CLASSES - Usmanova Mukhlisakhan Sobirovna; Akbaraliyeva is the daughter of Marjona Rakhmatillo (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article provides information on the history and current state of textile art, which is one of the types of folk crafts, in technology classes